Estimación indirecta de tasas de ingreso y de retiro de la actividad económica para México - Partida Bush, Virgilio (El Colegio de México A.C., 2011)
On the basis of information obtained from Mexico’s National Occupation and Employment Survey, attrition to and separation from activity rates have been calculated for the 32 states during 2000-2007 period. Ordinary least squares linear regressions are used to obtain equations to predict attrition and separation rates on the basis of participation rates in activity by age, given that this is the easiest type of information to obtain in population censuses or household sampling surveys. The results tally satisfactorily with comparable available figures. The algorithm is exemplified by the city of Zamora in 2000.